PERFORMANCE MANAGEMENT AS A MEDIA OF CHANGE TOWARDS ORGANIZATION IMPROVEMENT - Heru Kreshna Reza; Sukmo Hadi Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Management in an organization is the main activity that differentiates an organization from other organizations in providing services to humans. The success of an organization in providing services to its customers can be observed through the performance produced by the organization. The performance of an organization can be seen as good results if managerial performance and organizational performance can be combined, combining these two performances requires the organization to face changes. Change can occur because of something that comes from within or from outside an organization. Change management is an important thing in an organization. Change occurs through revolution, reform, evolution, and innovation. Everyone is certainly different in responding to change. Some of the responses included rejecting, being ignorant, not ready, and ready. The difference in these responses makes each person get different choices from change. Keywords: Performance Management, Change Management, Organization